Antiplatelet antibody‐induced thrombocytopenia does not correlate with megakaryocyte abnormalities in murine immune thrombocytopenia. (25th June 2018) - Guo, L.; Kapur, R.; Aslam, R.; Hunt, K.; Hou, Y.; Zufferey, A.; Speck, E. R.; Rondina, M. T.; Lazarus, A. H.; Ni, H.; Semple, J. W.
Abstract: Immune thrombocytopenia (ITP) is an autoimmune bleeding disorder characterized by increased peripheral immune platelet destruction and megakaryocyte defects in the bone marrow. Although ITP was originally thought to be primarily due to antibody‐mediated autoimmunity, it is now clear that T cells also play a significant role in the disease. However, the exact interplay between platelet destruction, megakaryocyte dysfunction and the elements of both humoral and cell‐mediated immunity in ITP remains incompletely defined. While most studies have focused on immune platelet destruction in the spleen, an additional possibility is that the antiplatelet antibodies can also destroy bone marrow megakaryocytes. To address this, we negated the effects of T cells by utilizing an in vivo passive ITP model where BALB/c mice were administered various anti‐αIIb, anti‐β3 or anti‐GPIb antibodies or antisera and platelet counts and bone marrow megakaryocytes were enumerated. Our results show that after 24 hours, all the different antiplatelet antibodies/sera induced variable degrees of thrombocytopenia in recipient mice. Compared with naïve control mice, however, histological examination of the bone marrow revealed that only 2 antibody preparations (mouse‐anti‐mouse β3 sera and an anti‐ αIIb monoclonal antibody (MWReg30) could affect bone marrow megakaryocyte counts. Our study shows that while most antiplatelet antibodies induce acute thrombocytopenia, the majority of them do not affect the number of megakaryocytes in the bone marrow. This suggests that other mechanisms may be responsible for megakaryocyte abnormalities seen during immune thrombocytopenia.